Effects of supplemental degradable intake protein on intake and digestibility of low-quality brome hay - Mathis, C.P.; Cochran, R.C.; Heldt, J.S.; Woods, B.C.; Stokka, Gerald L.; Olson, K. C.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The effects of increasing levels of degradable intake and digestion of low-quality brome hay were evaluated using 16 ruminally fistulated beef steers. Trends were evident for small, positive changes in total intake and digestion with increasing level of DIP supplementation. As a result, total digestible to feeding forage to provide .041, .082, and OM intake (TDOMI) increased with DIP supplementation but tended to plateau below the highest supplementation level.
Keywords: Beef; Steers; Forage; Intake; Digestion; Degradable intake protein